Programmable Multiwavelength Radio Frequency Spectrometry of Chemophysical Environments through an Adaptable Network of Flexible and Environmentally Responsive, Passive Wireless Elements. Issue 6 (27th March 2022) - Dautta, Manik; Hajiaghajani, Amirhossein; Ye, Fan; Escobar, Alberto Ranier; Jimenez, Abel; Dia, Kazi Khurshidi Haque; Tseng, Peter
Abstract : Readout of multiparametric environmental signals typically uses discrete sensing formats that individually require unique signal conditioning circuitry and/or processing pathways. Here, adaptable sensor networks composed exclusively of passive material architectures that enable spectrometric comonitoring of chemical or physical environmental signals are proposed. Herein, a single radio frequency (RF) reader wirelessly interacts first with an intermediate wireless relay coil—this is tunable in length and can be designed to conform around surfaces. This relay (that is fused on textiles or surfaces) is then wirelessly coupled to arrays of passive RF sensors with individually programmable flexibility/reactivity to environmental signals. Multiple chemical and physical signals can then be monitored within the single spectral readout of a wearable reader. This technique can probe over tunable length scales, and is robust to mechanical disturbances that limit present techniques. As a proof of concept, this approach is used to comonitor chemophysical metrics such as nutrients, temperature, pressure, pH, and more on the skin or in utensils with a single readout. This technique may form a cornerstone of zero‐microelectronic sensor networks. Abstract : Complex, multiparametric signals can be measured in a single spectral readout via an adaptable network of fully passive (and zero‐microelectronic) elements—such networks conform and flex along textiles or surfaces while enabling long distance and mechanically stable measurement of the chemophysical environment.